Factors influencing the groundwater circulation in Mali me Gropa karst massif, Central Albania - Eftimi, Romeo (Acta carsologica, 2025)
There are 23 carbonate karst areas in Albania with a total area of 6440 km2, or 24% of the country’s territory. Karst aquifers are the richest in the country and about 80% of the water supply for the population living in cities is supplied by karst water. One of the most interesting karst massifs of Albania is called Mali me Gropa (MMG) with a total surface area of 157 km2. It is the subject of this paper. Although this massif has attracted attention due to its exceptional development of surface karst landforms (karst pits, sinkholes, swallow holes) and its large and high-quality groundwater resources, it has not been the subject of comprehensive research. In this paper, for the first time, is a summary of the results of a combination of specialized studies, including geomorphological characterization, analysis of long-term groundwater regime observations in relationship with meteorological data, water balance studies applying the recently developed WaterbalANce software method, assessment of groundwater quality and its variability, determination of the groundwater flow velocity with an artificial tracer, and the use of hydrochemistry and runoff data to determine groundwater flow patterns and sensitivity of spring water to contamination. The results of the multi-method studies conducted on the MMG karst massif will inform future studies of the numerous carbonate karst regions in Albania. A final important objective of this article is to raise public awareness about the vulnerability of karst waters and the need to protect the associated ecosystem, especially now that the MMG karst massif is in the spotlight for tourism development.
Keywords: Albania; Albanija; aquatic resources; karst (geology); karst springs; kras (geologija); kraški izviri; padavine; precipitation (meteorology); vodni viri